Current landscape of innovative drug development and regulatory support in China - Ruirong Tan; Hua Hua; Siyuan Zhou; Zhimin Yang; Changming Yang; Guo Huang; Jin Zeng; Junning Zhao (Signal Transduction and Targeted Therapy)
Abstract The global pharmaceutical landscape remains dynamic and competitive, shaped by advancements in first-in-class therapies and breakthrough technologies. The United States has maintained its leadership in first-in-class therapies and breakthrough technologies, driven by advanced regulatory pathways, significant multinational corporation investments, a robust Research and Development (R&D) workforce, and continuous technological innovation. Additionally, global impact of the Food and Drug Administration (FDA) is further amplified through collaborations like Project Orbis, which facilitates simultaneous reviews of cancer treatments by multiple regulatory authorities worldwide. Europe, while historically strong, faces growing challenges in maintaining its competitive edge, particularly due to protracted regulatory timelines and complex coordination among its member states. In this competitive global environment, China has rapidly transformed from a generics-dominated market to a key player in innovative drug development. This article reviews China’s progress in innovative drug R&D from 2019 to 2023, emphasizing regulatory modernization, clinical trial advancements, and the emergence of novel therapies. By comparing China’s developments with above global counterparts, this review highlights the country’s achievements in regulatory efficiency, clinical trial progress, and the development of innovative therapies such as biologics and cell and gene therapies. Through this comparative analysis, the article underscores how China’s evolving policy-driven innovation ecosystem has positioned it as a growing leader in global drug development. The review examines how enhanced regulatory efficiency, clinical trial progress, manufacturing capabilities, and international collaboration have bolstered China’s growing influence, while also discussing the future opportunities and challenges it faces in shaping global pharmaceutical innovation and development.